Dyskurs edukacyjny w kształceniu przyszłych nauczycieli - Wiesława Burlińska, Wiesława Burlińska (Neofilolog, 2019)
In the training of future foreign language teachers discourse appears mainly in its theoretical dimension in relation to text discourse connected with teaching various skills. Discourse, however, might be also useful in the context of Teaching Practice. On the one hand, the analysis of classroom discourse could be used in deeper formative evaluation of the trainee. Analysis of this evaluational dialogue could support not only the growth of teaching strategies but could also significantly contribute to the formation of a reflective attitude of the future teacher. In this paper I present an analysis of a feedback session which refers to a lesson conducted by a teacher trainee form Bydgoszcz Teacher Training College of Foreign Languages and answer the question how useful this element can be in the creation of the reflective practitioner’s attitude.